2018
DOI: 10.3174/ajnr.a5851
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and Surgical Findings in Patients with Hemi-Laryngopharyngeal Spasm and the Potential Role of MRI in the Diagnostic Work-Up

Abstract: BACKGROUND AND PURPOSE:Hemi-laryngopharyngeal spasm is a recently discovered condition characterized by episodic coughing and unilateral throat contractions that may lead to severe stridor. These symptoms are caused by a vascular compression of the ipsilateral vagus nerve, typically the PICA. Microvascular decompression of the vagus nerve has been demonstrated to be a potential cure for this neurovascular compression syndrome. The main aim of this study was to clarify the role of MR imaging in the diagnostic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Our group has shown that the presence of a vascular conflict with the lower cranial nerves is common in the population. 3 This MRI finding is thus necessary but not sufficient for the diagnosis of HeLPS. Patients without a vascular conflict can be excluded from the diagnosis, but patients with this finding need further confirmatory tests.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our group has shown that the presence of a vascular conflict with the lower cranial nerves is common in the population. 3 This MRI finding is thus necessary but not sufficient for the diagnosis of HeLPS. Patients without a vascular conflict can be excluded from the diagnosis, but patients with this finding need further confirmatory tests.…”
Section: Discussionmentioning
confidence: 95%
“…All patients had magnetic resonance imaging of the head using a CISS sequence to assess for neurovascular conflict between the vagus nerve rootlets and the posterior inferior cerebellar artery on the ipsilateral side of the symptoms (Figure 1). 3 All patients were followed for at least 2 years post-operatively.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous MRI study reported that this incidental contact may be as high as 50% in asymptomatic individuals. 19 We are prospectively evaluating sequential unilateral proximal vagus nerve block as the diagnostic test of choice. Cessation of cough following a unilateral vagus nerve block ipsilateral but not contralateral to an MRI confirmed vascular compression may be the definitive test for VANCOUVER syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous MRI study reported that this incidental contact may be as high as 50% in asymptomatic individuals. 19 We are prospectively evaluating sequential unilateral proximal vagus nerve block The looping posterior inferior cerebellar artery (large arrow) had its convex apex against the caudal rootlet of the left vagus nerve (thin arrow) and was encroaching on the nerve from anterior and inferior (as predicted from the MRI). The vessel has been moved slightly laterally, out from behind the nerve, in order to see it.…”
Section: 'A Vagal Neuralgia Could Manifest As a Sudden And Exaggeratementioning
confidence: 99%
“…Honey et al proposed neurovascular compression of the vagus nerve rootlets identified on magnetic resonance imaging [ 21 ] as a potential cause of vagal dysfunction presenting in the larynx with sensory symptoms of abnormal throat sensations [ 22 ] associated with motor symptoms of laryngospasm/choking, neurogenic cough or intermittent stridor [ 23 ].…”
Section: Introductionmentioning
confidence: 99%